Peranan Kualitas Produk dan Kualitas Layanan Dalam Meningkatkan Loyalitas Pelanggan di Coffee Shop Sanatana Coffee & Eatery - Vina Oktaviani; Widiana Indah Permata (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the Role of Product Quality and Service Quality in Increasing Customer Loyalty at Sanatana Coffee & Eatery Coffee Shop. This research uses qualitative descriptive research methods. Respondents in this study were 10 respondents who were the Manager of Coffee Shop Sanatana Coffee & Eatery and 9 regular customers of Coffee Shop Sanatana Coffee & Eatery. The data collection methods used are observation, interviews, and documentation. The data collected were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of research conducted by conducting interviews show that the Role of Product Quality and Service Quality in Increasing Customer Loyalty at Sanatana Coffee Shop & Eatery is very good as evidenced by the color of the products sold at Sanatana Coffee & Eatery is very attractive, the shape and appearance of the products sold at Sanatana Coffee & Eatery are unique and aesthetic, the aroma and taste of the products sold at Sanatana Coffee & Eatery have their own characteristics, The reliability at Sanatana Coffee & Eatery is very good as seen from the ability to serve, the responsiveness possessed by Sanatana Coffee & Eatery is very good as seen from the fast response, the guarantee of Sanatana Coffee & Eatery given to customers is very detailed from the start of the taste, aroma and components used and the empathy given by Sanatana Coffee & Eatery to customers is very good as seen from the attitude shown which is very friendly and warm. Keywords: Product Quality, Service Quality, Customer Loyalty